Quantitative grain boundary analysis of bulk samples by SIMS - Christien, F; Downing, C; Moore, K; Grovenor, C (2013)
Solute grain boundary (GB) segregation is an important metallurgical phenomenon that has been extensively studied over the last 40 years, especially by Auger spectroscopy of fractured surfaces. More recently, it has been demonstrated that high-resolution SIMS (NanoSIMS) analysis can detect solute GB segregation on a simple polished cross-section. The aim of the work presented here was to demonstrate the use of SIMS to achieve quantitative analysis of GB segregation, including taking into account the inclination of the individual boundaries to the bulk sample surface. Copyright © 2012 John Wiley and Sons, Ltd. Copyright © 2012 John Wiley and Sons, Ltd.